2005
DOI: 10.1158/1078-0432.ccr-04-1458
|View full text |Cite
|
Sign up to set email alerts
|

SMAD4 as a Prognostic Marker in Colorectal Cancer

Abstract: More than 50% of patients with Dukes C colorectal cancer have disease recurrence and die within 5 years after surgical removal of their primary tumor. It is currently not possible to distinguish patients with good and bad prognosis. SMAD4 is an important tumor suppressor gene that mediates transforming growth factor-h superfamily signaling and is located in chromosome 18q21, a region with frequent genetic losses in these tumors. Allelic imbalance in 18q has been linked to poor prognosis in a subset of colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
148
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 40 publications
11
148
1
1
Order By: Relevance
“…(iii) Finally, a Kaplan–Meier survival analysis further narrowed down this list to 177 candidate tumor suppressors whose downregulation is negatively correlated with patient survival (and thus, likely to enhance tumor progression; see Materials and Methods, Fig 1A and Table EV3). Reassuringly, the resulting list includes several known colon tumor suppressors such as APC (Fearnhead et al , 2001; Aoki & Taketo, 2007), TCF7L2 (Hazra et al , 2008; Slattery et al , 2008), MCC (Kinzler et al , 1991), PTEN (Nassif et al , 2004; Song et al , 2012), and SMAD4 (Miyaki et al , 1999; Alazzouzi et al , 2005). It also includes 34 metabolic genes that are present in the human metabolic model (Table EV4), and which we further studied in the next modeling step.…”
Section: Resultsmentioning
confidence: 99%
“…(iii) Finally, a Kaplan–Meier survival analysis further narrowed down this list to 177 candidate tumor suppressors whose downregulation is negatively correlated with patient survival (and thus, likely to enhance tumor progression; see Materials and Methods, Fig 1A and Table EV3). Reassuringly, the resulting list includes several known colon tumor suppressors such as APC (Fearnhead et al , 2001; Aoki & Taketo, 2007), TCF7L2 (Hazra et al , 2008; Slattery et al , 2008), MCC (Kinzler et al , 1991), PTEN (Nassif et al , 2004; Song et al , 2012), and SMAD4 (Miyaki et al , 1999; Alazzouzi et al , 2005). It also includes 34 metabolic genes that are present in the human metabolic model (Table EV4), and which we further studied in the next modeling step.…”
Section: Resultsmentioning
confidence: 99%
“…They also classified patients into two groups according to the status of liver metastasis, and indicated a borderline significant correlation between Smad4 staining and liver metastasis (P ¼ 0.05) (Maitra et al, 2000). Alazzouzi et al (2005) studied 86 Dukes' C colorectal cancer patients and showed that patients with Dukes' C tumours expressing high Smad4 protein levels had significantly better overall (Po0.025) and disease-free (Po0.013) survival than patients with low levels by immunohistochemical staining. We, too, recently discussed the association between Smad4 level and prognosis in colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were evaluated as reported previously (Alazzouzi et al, 2005). To evaluate the intensity of Smad4 immunohistochemical staining, we used a semiquantitative scale, where 0 ¼ no Smad4 staining and 4 was the highest staining.…”
Section: Evaluation Of Smad4 Immunostainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to refine prognostication and predict the benefit derived from systemic treatment, several protein and genetic markers have been evaluated in patients with CRC, including allelic loss of chromosome 18q (Jen et al, 1994;Martinez-Lopez et al, 1998;Ogunbiyi et al, 1998;, absence of the deleted in colorectal carcinoma (DCC) protein (Shibata et al, 1996;Reymond et al, 1998;, decreased SMAD4 mRNA expression (Boulay et al, 2002;Alazzouzi et al, 2005), expression and/or abnormalities of cytoplasmic oncoprotein p53 (TP53) (Sun et al, 1992;Munro et al, 2005;Russo et al, 2005), protein levels and/or gene haplotype of thymidylate synthetase (TYMS) (Popat et al, 2004;Suh et al, 2005;Tsourouflis et al, 2008), microsatellite instability (MSI) (Gryfe et al, 2000;, and chromosomal instability (CIN) (Walther et al, 2008). Nevertheless, none of these biomarkers has been prospectively validated and established so far in clinical practice.…”
mentioning
confidence: 99%